Comparison of Mulligan’s, Alston’s and Prussian Blue Reaction’s Methods for Staining Dog Brain Slices Prior to Plastination - Vibulchan, Punnarat; Cheunsuang, Ornsiri (The Thai Journal of Veterinary Medicine, 2014)
To follow up our previous investigation of Sudan Red staining in plastinated brain specimen (Vibulchan et al., 2012), the present study aimed to examine staining dyes that can withstand the plastination procedures and be reserved in the specimen thereafter. Three staining methods, Mulligan’s method, Alston’s method and Prussian blue reaction method were tested in dog brain transverse slices. After the staining procedures the brain slices were dehydrated then forced impregnated using a polymer as described previously. The plastinated brain slices were compared for staining retention and analyzed for shrinkage. Results showed that Alston’s method of staining was preferable to dye preservation after plastination procedures. However, the shrinkage occurred with all three staining methods.